Penggunaan Metode Four Step Steinberg dalam Meningkatkan Kemampuan Membaca Permulaan Siswa dengan Gangguan Spektrum Autis - Eny Priana; Yulvia Sani; Annisa Purwanggi (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aimed to improve the early reading skills of a student with autism spectrum disorder through the Four Step Steinberg method. The study employed a Single Subject Research (SSR) approach with an A-B-A design consisting of baseline phase 1 (A1), intervention phase (B), and baseline phase 2 (A2). The participant was a fourth-grade student at SLB Sinar Hafizah. Data were collected through reading performance tests and systematic observations, then analyzed using visual analysis within and across conditions. The findings showed that the student’s early reading skills improved after the intervention. During phase A1, reading performance remained at 0%, then gradually increased from 12.5% to 93.75% at the end of the intervention phase. In phase A2, the performance remained stable at 93.75%, indicating a maintenance effect after the intervention was withdrawn. No overlap data were found between phases A1 and B (0%), indicating a functional relationship between the intervention and changes in reading behavior. These findings indicate that the Four Step Steinberg method is effective in improving and maintaining early reading skills in students with autism spectrum disorder.